leaf extracts compared to paracetamol on the body temperature of male rats exposed to bacterial infection (Sebha University Conference Proceedings, 2024)
This study aims to compare the biological effectiveness of polar extracts from the leaves of the Melia azedarach plant with each other, as well as to compare their effect with the drug paracetamol on the average body temperature of 90 Wistar albino rats exposed to bacterial infection. The rats were divided into 8 groups. The first group, which included 5 healthy animals, was designated as the negative control group. The remaining groups (G2-G8) were all injected with Staphylococcus aureus bacteria (100 µL) behind the neck. G2 consisted of 5 infected animals that received no treatment and was designated as the positive control group. G3 also contained 5 infected animals but was treated with paracetamol at a daily oral dose of 100 mg/kg body weight for 3 days.For the remaining groups (G4-G8), each group contained 15 animals, divided into 3 sub-groups. Each sub-group was exposed to one of three concentrations (100, 250, or 500 mg/kg body weight) of a specific leaf extract, varying in polarity. The extracts used were hexane (G4), petroleum ether (G5), chloroform (G6), acetone (G7), and ethanol (G8), administered once daily for 3 days. At the end of the experiment, blood samples were collected.The results of the study revealed a significant decrease in average body temperature (P acetone > petroleum ether > chloroform > hexane. The hexane extract was the least biologically effective in reducing the average temperature, and the decrease in temperature was observed to be concentration-dependent across all extracts.